Whispering a wish into the ears of Nandi - Mumbai Archive Project Team (Jio Institute, 2024)
A young girl whispers a wish into the ears of Nandi, the mount and messenger of Lord Shiva. For a wish to be fulfilled, it must be made in secret by cupping one's hand over the ear and whispering so others may not hear it.